The north-west Borneo trough - Hutchison, C.S. (Elsevier, 2010)
The North-West Borneo Trough is bordered along its south-east margin by a melange wedge that has been the subject of disagreement with insufficient discussion. Offshore Palawan it has been interpreted as an accretionary prism that has been preserved in place when subduction ceased in the Middle Miocene. It is unconformably overlain by undeformed Upper Miocene to Holocene draping strata. Farther south-west along the Trough, the seismically identical melange wedge has been named a Major Thrust Sheet System, which was assumed to have been thrust as a nappe north-westwards over the autochthonous Dangerous Grounds terrane of attenuated continental crust of the South China Sea passive margin.